PENGUATAN KEPEMIMPINAN PENDIDIKAN VISIONER DALAM MENJAWAB TANTANGAN GLOBAL ABAD 21 - Siswadi Siswadi (STKIP Pesisir Selatan, 2024)
This study aims to examine the visionary leadership strategies of school principals in responding to the challenges of 21st-century education. The background of this research stems from the urgent need for adaptive, transformative, and contextual leadership in facing global dynamics characterized by technological advances, globalization, and the complexity of student needs. The research used a qualitative approach with a library research study. Data was obtained through analysis of various relevant books, journal articles, and academic documents. The results show that principals with a visionary leadership style are able to formulate an inspiring long-term vision, internalize the values of the vision throughout the school community, and implement collaborative and innovative strategies, such as strengthening school culture, developing teacher capacity, and utilizing educational technology. The findings also show that visionary principals are responsive to changes in the needs of constituents, proactive in building partnership networks, and make ethical and moral values the basis of leadership.